Dr. Takamasa Nakai — Deep Plane Facelift — Tokyo - Nakai, Takamasa (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Takamasa Nakai, practicing in Tokyo, Japan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003082; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; japan; tokyo